Tecnologia socioeducativa para a prevenção do câncer do colo do útero: um estudo metodológico - Maria Verbene Costa Aguiar; Maria de Nazaré de Souza Ribeiro; Cleisiane Xavier Diniz (Online Brazilian Journal of Nursing, 2026)
Objective: To develop and validate a socio-educational technology in the format of an audiovisual series composed of five videos, aimed at preventing cervical cancer in women aged 20 to 40. Method: A methodological study with a mixed-methods approach, conducted in two stages: development and validation of audiovisual technology. Development was based on a scoping review according to the Joanna Briggs Institute, with searches in national and international databases and gray literature. Technical-scientific validation was performed with 22 specialist nurses using the Content Validity Index (≥0.70), and the illustrative dimension was evaluated by five designers using the Suitability Assessment of Materials. Analysis included descriptive statistics and thematic analysis of suggestions. Results: The review provided the basis for five thematic scripts. The global Content Validity Index was 0.96, indicating high agreement among specialists. Illustrative validation reached 96.9% adequacy, demonstrating technical-scientific quality and sociocultural suitability. Conclusion: The technology demonstrated content validity and illustrative quality, with potential for use in health education actions. Future evaluation with the target audience is recommended.